2006
DOI: 10.1128/jvi.01212-06
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 Vpr Induces DNA Replication Stress InVitro and In Vivo

Abstract: The human immunodeficiency virus type 1 (HIV-1) viral protein R (Vpr) causes cell cycle arrest in G 2 . Vpr-expressing cells display the hallmarks of certain forms of DNA damage, specifically activation of the ataxia telangiectasia mutated and Rad3-related kinase, ATR. However, evidence that Vpr function is relevant in vivo or in the context of viral infection is still lacking. In the present study, we demonstrate that HIV-1 infection of primary, human CD4؉ lymphocytes causes G 2 arrest in a Vpr-dependent mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 64 publications
2
100
0
Order By: Relevance
“…Recently, Zimmerman et al reported that HIV-1 infection in primary human CD4+ lymphocytes results in ATR-dependent G 2 arrest and accumulation of RPA, which suggests the presence of stalled replication forks (Zimmerman et al, 2006). Consistent with a model in which Vpr activates the ATR DNA damage response pathway, Yuan et al found that Vpr activates the negative regulator of Cdk1, Wee1 (Yuan et al, 2003).…”
Section: Mechanisms To Explain Vpr-induced G 2 Arrestmentioning
confidence: 88%
See 2 more Smart Citations
“…Recently, Zimmerman et al reported that HIV-1 infection in primary human CD4+ lymphocytes results in ATR-dependent G 2 arrest and accumulation of RPA, which suggests the presence of stalled replication forks (Zimmerman et al, 2006). Consistent with a model in which Vpr activates the ATR DNA damage response pathway, Yuan et al found that Vpr activates the negative regulator of Cdk1, Wee1 (Yuan et al, 2003).…”
Section: Mechanisms To Explain Vpr-induced G 2 Arrestmentioning
confidence: 88%
“…Recently, Sakai et al reported that deletion of Vpr, in addition to Vif, rendered HIV-1 incapable of causing G 2 arrest and eliminated the cytopathic properties of the virus, which suggests a link between viral cytopathicity and cell cycle arrest (Sakai et al, 2006). Recently, infected lymphocytes (identified by expression of Gag p24) isolated from recent HIV-1 seroconverters and stained with propidium iodide for DNA content were found to be arrested in G 2 , indicating that G 2 arrest is not merely an in vitro phenomenon (Zimmerman et al, 2006).…”
Section: Vpr-induced G 2 Arrest and Viral Replicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several viruses, including DNA virus herpes simplex v i r u s ( H S V ) [ 1 4 , 1 5 ] , K a p o s i 's s a r c o m a -a s s o c i a t e d herpesvirus [16] , human cytomegalovirus (HCMV) [17] Epstein-Barr virus (EBV) [18] , papillomavirus [19,20] , simian virus 40 (SV40) [21] and retrovirus HIV [22][23][24] , trigger cellular signaling cascades that are characteristic of a DNA damage response. Infection and replication of HBV have been achieved in human hepatoma cell lines and primary fetal human hepatocytes using transfected HBV genomes or HBV serum.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Epstein-Barr Virus (EBV) [16] abrogates the p53 checkpoint signaling pathway through the interaction of the BZLF1 protein and p53 to avoid apoptosis. Other vir uses such as human immunodeficiency virus type 1 (HIV-1) [17][18][19][20] , herpes simplex virus type 1 (HSV-1) [21,22] and human cytomegalovir us [23] can activate and exploit a cellular DNA damage response, which aids viral replication. Adenovirus blocks ATM signaling and concatemer formation through targeting the DNA repair complex of MRN for degradation and mislocalization [24,25] .…”
Section: Introductionmentioning
confidence: 99%